Do Images of Biskyrmions Show Type‐II Bubbles?. Issue 16 (7th March 2019) - Loudon, James C.; Twitchett‐Harrison, Alison C.; Cortés‐Ortuño, David; Birch, Max T.; Turnbull, Luke A.; Štefančič, Aleš; Ogrin, Feodor Y.; Burgos‐Parra, Erick O.; Bukin, Nicholas; Laurenson, Angus; Popescu, Horia; Beg, Marijan; et al.
Abstract: The intense research effort investigating magnetic skyrmions and their applications for spintronics has yielded reports of more exotic objects including the biskyrmion, which consists of a bound pair of counter‐rotating vortices of magnetization. Biskyrmions have been identified only from transmission electron microscopy images and have not been observed by other techniques, nor seen in simulations carried out under realistic conditions. Here, quantitative Lorentz transmission electron microscopy, X‐ray holography, and micromagnetic simulations are combined to search for biskyrmions in MnNiGa, a material in which they have been reported. Only type‐I and type‐II magnetic bubbles are found and images purported to show biskyrmions can be explained as type‐II bubbles viewed at an angle to their axes. It is not the magnetization but the magnetic flux density resulting from this object that forms the counter‐rotating vortices. Abstract : Research on skyrmions has yielded reports of biskyrmions: bound pairs of counter‐rotating vortices of magnetization. This study combines electron microscopy, X‐ray holography, and simulations to investigate biskyrmions in MnNiGa. It demonstrates that images of biskyrmions can be explained as type‐II magnetic bubbles. It is not the magnetization but the magnetic flux density from this object that forms the counter‐rotating vortices.